2013
DOI: 10.1111/jmi.12088
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic characterization of defect structure in RDX crystals

Abstract: Summary Three batches of the commercial energetic material RDX, as received from various production locations and differing in sensitivity towards shock initiation, have been characterized with different microscopic techniques in order to visualize the defect content in these crystals. The RDX crystals are embedded in an epoxy matrix and cross‐sectioned. By a treatment of grinding and polishing of the crystals, the internal defect structure of a multitude of energetic crystals can be visualized using optical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The root-mean-square (rms) roughness of the HMX@PDA surface was 36.03 nm, whichw as less than that of the HMX surface (68.45 nm). The opticali mages of the HMX and HMX@PDA particles showed some internal defects, which could become hot spots for the crystals under mechanical stimulus [22] (Figure 3a nd Figure S2, Supporting Information). The images fort he HMX@PDA particles indicated that the PDA coating was typically thin as the light could transmitt he as-prepared crystals (Figure 3b).…”
Section: Morphologies Of the Original Hmx And As-prepared Hmx@pda Parmentioning
confidence: 98%
“…The root-mean-square (rms) roughness of the HMX@PDA surface was 36.03 nm, whichw as less than that of the HMX surface (68.45 nm). The opticali mages of the HMX and HMX@PDA particles showed some internal defects, which could become hot spots for the crystals under mechanical stimulus [22] (Figure 3a nd Figure S2, Supporting Information). The images fort he HMX@PDA particles indicated that the PDA coating was typically thin as the light could transmitt he as-prepared crystals (Figure 3b).…”
Section: Morphologies Of the Original Hmx And As-prepared Hmx@pda Parmentioning
confidence: 98%
“…In addition more advanced microscopic techniques have been applied, using e.g. confocal scanning laser microscopy (CSLM) for improved characterization of the inclusion content in several RDX batches 7, showing that for some of the RDX batches (i.e. K1, K6, and K7) the inclusions are mainly present in the periphery of the energetic particles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this Round Robin program, these selected RDX grades were also characterized as part of other research studies, as reported in Refs. 710. Since the Floret test requires only small amounts of material, allows it to be used as a quick reference test.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic wave propagation and behavior can lead to local failure mechanisms, at the microstructural level, such as void coalescence, crack nucleation, and crack propagation [14][15][16][17][18]. Understanding the mechanisms by which local failure occurs in energetic materials, under dynamic loading conditions, is paramount, due to the material competition between dynamic crack nucleation, propagation, and plastic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work by Bouma et al [15] has shown that energetic RDX crystals contain cracks and voids due to processing. Palmer and Field [16] showed experimentally that under compressive loading of HMX energetic crystals, twinning occurs, and this typically precedes crystal fracture.…”
Section: Introductionmentioning
confidence: 99%